Improving Learning Design Using Learning Analytics in Relation to Study Experience - Satu Aksovaara; Sami Määttä; Tommi Kärkkäinen; Minna Silvennoinen (Seminar.net)
In higher education, the learner-centered approach faces challenges due to the growing number and diversity of students and the increasing complexity of course delivery. Study experiences, which correlate with academic achievement, may be enhanced through learning analytics. In particular, analytics can offer valuable, timely insights by collecting and analyzing data on the study experiences and student-related metrics. This allows teachers to gain understanding of students' psychological qualities, which are not typically inferred from standard learning management systems.